Testosterone: from basic research to clinical applications - Smith, Lee B. (SpringerBriefs in reproductive biology,, 2013)
This volume provides a brief résumé of the history of testosterone research, from the early pioneers through to the most recent advances in the field. We discover how steroid hormones were first identified and how testosterone was shown to be essential for male development. Moving forward we explore how and where testosterone is produced, and how the body controls testosterone production. We then investigate the impact testosterone has on different body systems both during their development and function, and how perturbation of testosterone action is associated with disease. We complete our story with an exploration of the emerging roles of testosterone in clinical therapy, and the future potential for manipulation of the testosterone signaling system for human health benefit.